Evaluation of the rationality of drugs use inpatient patients with type 2 diabetes mellitus of 2023 at Hospital Y Depok - Khairani, Sondang; Manninda, Reise; Wijayanti, Bitya Aulia (Faculty of Pharmacy, Universitas Pancasila, 2025)
Diabetes mellitus is a chronic disease caused by failure to control blood glucose levels. Type 2 Diabetes Mellitus (T2DM) is a condition of hyperglycemia caused by the failure of insulin to maintain balanced blood sugar levels. If T2DM is not treated it will cause complications. One way to control T2DM is the rational use of antidiabetic drugs. This study aims to look at the demographic data of inpatients with T2DM, patterns of drug use, rationality for drug use, and the relationship between the rationality of drug use and therapeutic outcomes in inpatients with T2DM at Hospital Y Depok for the period 2023. The outcome evaluated is a random blood sugar test. The research method was carried out descriptively and inferentially with a cross-sectional design. There were 122 samples that met the inclusion criteria, women predominantly suffered from type 2 diabetes mellitus (50.89%). The most common age range was 46-65 years (64.56%). As many as 84.31% of patients used the JKN payment method. The most widely used class of type 2 diabetes mellitus medication is insulin. In evaluating the rationality of using type 2 diabetes mellitus drugs, the rationality results were 99.49% correct drug, 100% correct dose, and 98.73% correct administration. The results of statistical tests show that there is a correlation between the rationality of drug use and clinical outcomes p-value 0.001.